Sensitive periods for 17β‐estradiol exposure during immune system development in sea bass head kidney. Issue 6 (16th August 2015) - Seemann, Frauke; Knigge, Thomas; Duflot, Aurélie; Marie, Sabine; Olivier, Stéphanie; Minier, Christophe; Monsinjon, Tiphaine
Abstract: An increasing body of evidence suggests that sex steroids play an important role in the development and regulation of vertebrate immune defense. Therefore, compounds with estrogenic activity may influence the immune system via receptor‐mediated pathways. The presence of estrogen receptors in immune cells and organs during the early stages of development may indicate that female steroid hormones are involved in the maturation of the fish immune system. This is of particular importance, as some marine fish are probably exposed to sources of exogenous estrogens while they reside in their estuarine nursery grounds. In this study, the influence of 17β‐estradiol (E2) on estrogen receptor and cytokine gene expression was assessed in juvenile sea bass ( Dicentrarchus labrax ) together with characterization of the head kidney leukocyte populations and corresponding phagocytic activity during organ regionalization from 98 to 239 dph. E2 exposure, beginning at 90 dph resulted in indirect and delayed modifications of interleukin 1β and estrogen receptor α gene expression, which may affect B‐lymphocyte proliferation in the sea bass head kidney. The E2 treatment of 120 dph fish led to an increase in estrogen receptor β2 and a decrease in transforming growth factor β1 gene expression, which coincided with decreased phagocytic activity of head kidney lymphocytes and monocytes/macrophages. Additionally, these changes were observed during developmental periods described as critical phases for B‐lymphocyte development in mammals. Consequently, exogenous estrogens have the potential to modify the innate immune response in juvenile sea bass and to exert detrimental effects on head kidney development. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The influence of 17β‐estradiol (E2) on estrogen receptor and cytokine gene expression, leukocyte populations and phagocytic activity was assessed in the juvenile sea bass ( Dicentrarchus labrax ) head kidney during organ regionalization from 98 to 239 dph. E2 exposure, beginning at 90 dph resulted in indirect and delayed modifications of interleukin 1β and estrogen receptor α gene expression, which may affect B‐lymphocyte proliferation. The E2 treatment of 120 dph fish led to an increase in estrogen receptor β2 and a decrease in transforming growth factor β1 gene expression, which coincided with decreased phagocytic activity of head kidney lymphocytes and monocytes/macrophages.